When does word frequency influence written production? - Baus, Cristina; Strijkers, Kristof; Costa, Albert (Frontiers in Psychology, 2013)
The aim of the present study was to explore the central (e.g., lexical processing) and peripheral processes (motor preparation and execution) underlying word production during typewriting. To do so, we tested non-professional typers in a picture typing task while continuously recording EEG. Participants were instructed to write (by means of a standard keyboard) the corresponding name for a given picture. The lexical frequency of the words was manipulated: half of the picture names were of high-frequency while the remaining were of low-frequency. Different measures were obtained: 1) first keystroke latency and 2) keystroke latency of the subsequent letters and duration of the word. Moreover, ERPs locked to the onset of the picture presentation were analysed to explore the temporal course of word frequency in typewriting. The results showed an effect of word frequency for the first keystroke latency but not for the duration of the word or the speed to which letter were typed (interstroke intervals). The electrophysiological results showed the expected ERP frequency effect at posterior sites: amplitudes for low-frequency words were more positive than those for high-frequency words. However, relative to previous evidence in the spoken modality, the frequency effect appeared in a later time-window. These results demonstrate two marked differences in the processing dynamics underpinning typing compared to speaking: First, central processing dynamics between speaking and typing differ already in the manner that words are accessed; second, central processing differences in typing, unlike speaking, do not cascade to peripheral processes involved in response execution.